Financial Dollarization: Trojan Horse for Ukraine? - Versal, Nataliia; Stavytskyy, Andriy (Ekonomika, 2015)
The paper revisits the causes and consequences of financial dollarization in Ukraine during the past decade (monthly data). Dollarization in emerging markets plays a dual role: positive and negative. This study of financial dollarization is in the context of resident household holdings of foreign currency-denominated bank deposits and loans. If exchange rates are stable, deposit dollarization allows the withdrawal of money from the shadow economy, and loan dollarization allows the lending of long-term money, which is not possible with domestic currency due to inflation expectations. At the same time, the instability and lack of supply of foreign currencies in the market result in the collapse of household and bank finances, leading to currency risk, credit risk, and liquidity risk. Therefore, the study uses estimate indicators, the deposit dollarization index (DDI), household foreign currency deposits and loans, loan to deposit ratio (LTD), and inflation to find out the tendencies in the context of a changing domestic currency exchange rate. We present three models to reveal the influence of financial dollarization on banking stability. The first one explains the real value of domestic currency deposits through indicators such as M2 (positive), exchange rate (negative), domestic currency deposits (positive), and panic effects (negative). The second one describes the influence of the exchange rate (negative) and panic effects (negative) on foreign currency deposits. The third one explains the DDI through such the exchange rate, M2, and interest rates. The combined models provide an insight about the time necessary to stabilize the Ukrainian banking system.
Keywords: financial dollarization; financial intermediation; foreign exchange rate; emerging markets; financial fragility; banking stability